Evaluating Pain Relief Using Total Pain Relief (Totpar) In Operative Orthopedic Patients - Begum, Syeda Zuleqaunnisa; Chukka, Saritha; Akram, Mohd (Journal of Neonatal Surgery, 2025)
Background: Postoperative pain is a major concern for orthopedic patients, as it can delay recovery and prolong rehabilitation. This study aimed to evaluate the efficacy of pain relief using the Total Pain Relief (TOTPAR) score in postoperative orthopedic patients. Additionally, it aimed to analyze the role of multimodal analgesia in improving pain management and enhancing recovery outcomes. Methods: A prospective observational study was conducted involving 148 patients who underwent various orthopedic surgeries. Pain levels were assessed using the Numerical Rating Scale (NRS) and the TOTPAR score over a 48-hour period following surgery. Standardized analgesic regimens, including nonsteroidal anti-inflammatory drugs (NSAIDs), opioids (e.g., tramadol), and adjunctive therapies, were administered to manage postoperative pain. The effectiveness of these analgesic treatments was measured by changes in NRS and TOTPAR scores. Results: The study found a significant reduction in postoperative pain intensity. NRS scores decreased from a mean of 7.77±0.72 before treatment to 6.66±0.71 after treatment, indicating notable pain relief. The TOTPAR scores showed consistent improvement, rising from a baseline of 0.24±1.71 to 32.14±6.13 at 48 hours, further demonstrating the effectiveness of pain management. NSAIDs were the most commonly used analgesics, followed by tramadol and other adjuncts, supporting the role of multimodal analgesia in postoperative pain relief. However, no significant correlation was found between the TOTPAR score and the length of hospital stay, suggesting that factors other than pain relief may influence recovery duration. Conclusion: The study concluded that the TOTPAR score is a reliable and comprehensive tool for evaluating postoperative pain relief in orthopedic patients. The findings underscore the importance of individualized pain management strategies and the effectiveness of multimodal analgesia in optimizing pain control and improving recovery outcomes. By utilizing a combination of analgesic approaches, healthcare providers can better address postoperative pain and enhance the patient experience during recovery.